Economic Education Analysis: The Relationship Between Education Investment And Labor Productivity - Apud Abdul Aziz; Adie Kusna Wibowo (PT. ALHAFI BERKAH INDONESIA, 2025)
This study analyzes the relationship between education investment and labor productivity in Indonesia using panel data from 5 provinces during the period of 2021-2023 with a two-way fixed effects model. The main findings indicate that education investment has a positive and significant effect on productivity, with an optimal time lag of 2 years. Vocational education has the highest return on investment (ROI) at 12.7% compared to general education at 8.3%. The student-teacher ratio has a negative impact if it exceeds 1:20, especially in underdeveloped areas, while education infrastructure has a positive effect, reinforced by digitalization (+23% moderating effect). Spatial analysis shows disparities in productivity across regions, with the elasticity of education investment in Java-Bali (0.45) being higher than in Eastern Indonesia (0.28). The productivity gap between DKI Jakarta and Papua reached 1.96 times in 2023. Policy implications include more targeted allocation of education budgets, optimization of teacher distribution, and development of vocational education infrastructure. This study also recommends a performance-based funding formula. Theoretically, this research contributes to the development of an educational production function model specific to Indonesia, provides empirical evidence of the threshold effect of education investment, and offers a comparative analysis of ROI. Limitations of the study include a limited scope of informal sector data and the use of proxy variables for teacher quality. These findings are relevant for national education policy and suggest further research that integrates micro-level data and indicators of technology adoption.